Upaya Pengendalian Tekanan Darah Melalui Pengelolaan Diet Hipertensi - Ernawati Ernawati; Istianah; Baik Heni Rispawati; Hapipah; Maelina Ariyanti; Heny Marlina Riskawaty; Bahjatun Nadrati (Fakultas Pertanian, 2026)
Hypertension is a non-communicable disease characterized by a persistent increase in blood pressure due to the interaction of genetic factors and lifestyle, especially a diet high in sodium and low in fiber and essential minerals. Consumption of processed foods and high salt intake causes fluid retention, increased peripheral resistance, and activation of the renin-angiotensin-aldosterone system, which maintains elevated blood pressure. This community service activity aims to increase the knowledge of hypertension patients about the DASH diet to help control high blood pressure and stabilize it. The target of the activity is hypertension patients in Motong Are Village, Kediri, West Lombok, totaling 15 people; hypertension patients were gathered, then provided with material related to the DASH diet. The stages of implementing this community service activity are divided into 3 sessions, namely the first session measuring the blood pressure of hypertension sufferers, the second session delivering material related to the DASH diet, and the third session evaluating the understanding of hypertension sufferers regarding the DASH diet that has been presented to control blood pressure. The results of this service had a positive impact, namely an increase in knowledge and understanding of hypertension sufferers in managing the DASH diet to help control blood pressure